2010
DOI: 10.2215/cjn.03040509
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Epoetin Alfa Dose and Mortality

Abstract: Conclusions: There is appreciable CBI at higher EPO doses, and EPO dose was not associated with increased mortality in marginal structural model analyses that more completely addressed this confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Zhang et al [8] analyzed elderly hemodialysis patients and reported that relative to doses between 20,000 and 30,000 IU/week, relative hazards for other doses were less than 1, although they lacked statistical significance. Wang et al [10] analyzed adult patients receiving hemodialysis from a single provider and reported that relative to doses between 0 and 7,000 IU/week during a 2-week period, the relative hazard for no EPO was 1.72 and that hazard ratios for larger doses were almost 1. These studies and the current study cannot be easily reconciled.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhang et al [8] analyzed elderly hemodialysis patients and reported that relative to doses between 20,000 and 30,000 IU/week, relative hazards for other doses were less than 1, although they lacked statistical significance. Wang et al [10] analyzed adult patients receiving hemodialysis from a single provider and reported that relative to doses between 0 and 7,000 IU/week during a 2-week period, the relative hazard for no EPO was 1.72 and that hazard ratios for larger doses were almost 1. These studies and the current study cannot be easily reconciled.…”
Section: Discussionmentioning
confidence: 99%
“…Misspecification of the model of ESA dose may be relevant. Wang et al [10] specified an ordinal logistic regression model of dose, categorized as none or by quartile. This model supposes homogeneity of predictors of administration and dose (given administration), but we found marked differences in these sets of predictors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Furthermore, not all studies implicate ESA exposure in explaining risk; a recent study using marginal structural modeling failed to report an association between high ESA dosage and adverse outcome. 23 Conversely, a secondary analysis of the CHOIR study, using landmark analysis as a way to avoid some of the biases inherent in observational studies, demonstrated that high ESA dosage was an independent predictor of the combined end point of mortality, nonfatal MI, heart failure, and stroke. 17 In this analysis, targeting a higher Hb or lower Hb with higher dosages of ESA associates with poor outcomes, whereas achieving a higher Hb improves outcomes.…”
mentioning
confidence: 99%